The effect of a home exercise intervention on persons with lower limb amputations: a randomized controlled trial. (January 2020) - Godlwana, Lonwabo; Stewart, Aimee; Musenge, Eustasius
Objective: To establish if a home-based exercise and education programme is more effective than usual treatment in improving function, mobility and quality of life in people with lower limb amputation due to peripheral vascular disease. Method: A blocked randomized single-blinded controlled trial (RCT) with 154 participants (54 female; mean age 58) compared a home-based exercise and education programme (n = 77) with usual care (control) (n = 77). Participants were measured at baseline, immediately post intervention at three months, and after a further three months without any intervention. The outcome measures were the Barthel Index, Participation Scale, EuroQuol 5D, Modified Locomotor Capability Index and Timed Up and Go Test. Changes over time were established using generalized estimating equations and analysis of covariance, ( P  < 0.05) Results: The Participation Scale (18.73 ± 14.91 against 26.67 ± 19.14; P  = 0.011), the EuroQuol5D visual analogue scale (69.10 ± 20.31 against 55.37 ± 27.67; P  = 0.003), EuroQuol5D utility index (0.672 ± 0.300 against 0.532 ± 0.358; P  = 0.25) and the Modified Capability Index (21.03 ± 15.79 against 15.91 ± 13.67; P  = 0.034) improved in the intervention group compared with the control group at three months. At six months, there was no difference between the groups in any of the measures except for the EuroQuol5D visual analogue scale (74.52 ± 16.14 against 66.34 ± 22.91; P  = 0.033). Although there were no differences between the Timed Up and Go test at 3 (35.39 ± 32.48 against 45.08 ± 41.52; P  = 0.192) and six months (28.22 ± 20.96 against 36.08 ± 36.19; P  = 0.189) between the groups the intervention group was more mobile. Conclusion: This intervention improved function, mobility and quality of life in persons following lower limb amputation in the first three months post amputation.